Comparison of Infant Test-Weighing and Hourly Breast Expression in Measuring Maternal Milk Production (P11-041-19). (13th June 2019) - Roznowski, Dayna; Wagner, Erin; Riddle, Sarah; Nommsen-Rivers, Laurie
Abstract: Objectives: Measuring maternal milk production is cumbersome. Our objectives were to: 1) confirm that milk production rate reaches steady state at hour 2 of hourly breast emptying; and 2) compare agreement in milk production when measured using the well-established test-weighing method versus the more efficient hourly breast emptying method (Lai, et al., Breastfeeding Medicine, 2010). Methods: Eligible mothers were 4–10 weeks postpartum and exclusively breastfeeding their healthy, singleton, term infants. A subset of mothers test-weighed (TW ) their infant (± 2 g) before and after breastfeeding for 48h. Within 1 week of TW, mothers had a morning visit at the research clinic for hourly breast expression measurements. Mothers emptied both breasts at baseline (h0), and 1, 2, and 3 hours after baseline (h1, h2, h3) using a hospital-grade pump. We recorded hourly milk output ± 1 g and adjusted production rate (g/h) to exact interval (minutes from end of previous to end of current expression). We used paired t-test to compare g/h at h3 versus h0, h1, and h2. We estimated mother's steady-state milk production rate (MPR, g/h) as mean (h2, h3). We used the Bland-Altman method for determining the 95% limits of agreement in measuring milk production (g/24h) using TW versus MPRx24. Results: 23 mothers (65% primiparous) were 54 ± 14 days postpartum. Milk output was 185 ± 55 g at h0 and 60 ± 26, 47 ± 13, 44 ± 13 g/h at h1, h2, and h3, respectively. Mean paired difference (vs. h3) was significant at h0 and h1 ( P  < 0.05), but not at h2 ( P  > 0.05, h3 - h2 = 3 ± 10 g/h). In the subset with TW data (n = 16), mean TW milk output was 717 ± 119 g/24h, and mean MPRx24 was 1085 ± 300 g/24h. Mean difference, MPRx24 - TW [± 95% limits of agreement], was 368 [± 468] g/24h; and mean ratio, MPRx24/TW, was 1.5 [± 0.4]. Both difference and ratio significantly increased as MPR increased ( P  < 0.05). Conclusions: Hourly milk production reaches steady state at h2; thus, mean (h2, h3) is a valid measure of current maternal milk production capacity. However, there was not homogeneous agreement between MPR and TW, and the 95% limits of agreement were very wide: -91 to 459 g/24h when expressed as the difference, and 0.9 to 1.9-fold as a ratio. Thus, MPR is feasible for researching variation in maternal milk production but not for researching variation in infant intake. Funding Sources: None. Supporting Tables, Images and/or Graphs: